Postoperative Cognitive Dysfunction and Alzheimer’s Disease: A Transcriptome-Based Comparison of Animal Models - Wang, Yi-Wei; Wang, Liang; Yuan, Sheng-Jie; Zhang, Yuan; Zhang, Xin; Zhou, Le-Ting (Frontiers in Aging Neuroscience, 2022)
Background Postoperative cognitive dysfunction (POCD) is a common complication characterized by a significant cognitive decline. Increasing evidence suggests an association between the pathogenesis of POCD and Alzheimer’s disease (AD). However, a comprehensive understanding of their relationships is still lacking. Methods First, related databases were obtained from GEO, ArrayExpress, CNGB, and DDBJ repositories. De novo analysis was performed on the raw data using a uniform bioinformatics workflow. Then, macro- and micro-level comparisons were conducted between the transcriptomic changes associated with AD and POCD. Lastly, POCD was induced in male C57BL/6j mice and the hippocampal expression levels of mRNAs of interest were verified by PCR and compared to those in AD congenic models. Results There was a very weak correlation in the fold-changes in protein-coding transcripts between AD and POCD. Overall pathway-level comparison suggested that AD and POCD are two disease entities. Consistently, in the classical AD pathway, the mitochondrial complex and tubulin mRNAs were downregulated in both the POCD hippocampus and cortex. POCD and AD hippocampi might share the same pathways, such as tryptophan metabolism, but undergo different pathological changes in phagosome and transferrin endocytosis pathways. The core cluster in the hippocampal network was mainly enriched in mitosis-related pathways. The hippocampal expression levels of genes of interest detected by PCR showed good consistency with those generated by high throughput platforms. Conclusion POCD and AD are associated with different transcriptomic changes despite their similar clinical manifestations. This study provides a valuable resource for identifying biomarkers and therapeutic targets for POCD.